Penerapan Metode Diskusi untuk Meningkatkan Hasil Belajar Pendidikan Agama Buddha pada Siswa Kelas VII SMP Maitreyawira Dumai - Ahong Ahong; Hosan Hosan (STAB Maitreyawira, 2024)
The purpose of this action research is to determine the implementation of learning and the application of the discussion method to improve learning outcomes of Buddhist education in class VII students of SMP Maitreyawira Dumai. The results of the research with the procedures for planning, implementing, observing, and reflecting. It has been implemented well, which is indicated by the increase in learning outcomes and character understanding, the average score of students shows an increase in understanding from 70 in the pre-cycle increasing to 73 in the first cycle, increasing to 90 in the second cycle until all students complete (≥74 KKM ) in receiving character-based Buddhist lessons, in percentage there was an increase in understanding of 20% in the first cycle and 30% in the second cycle to 100%. This shows that the application of the discussion method was successfully understood by the students, the Buddhist teacher was more involved in the activeness of students in learning with the discussion method with a seating arrangement pattern which was considered effective and enjoyable.